The Profiling Serum Cytokines as Stage-Specific Biomarkers for Endometriosis: A Cross-Sectional Study for Non-Invasive Staging: IL-8, TNF-α, VEGF-A, IL-1β, MCP-1, IL-10, IL-17A, and IFN-γ - Liu, Jianying; Lai, Huichao (Journal of Medical Biochemistry, 2026)
-